Coinfection of COVID-19 and Tuberculosis in Uganda - Nuwagira, Edwin; Mpagama, Stellah G.; Katusiime, Asumpta; Natamba, Bobson; Baluku, Joseph Baruch; Lai, Peggy S. (The American Journal of Tropical Medicine and Hygiene, 2023)
The clinical features and outcomes of tuberculosis (TB) and COVID-19 coinfection are not well established. This short report describes 11 people with TB/COVID-19 coinfection in Uganda. The mean age was 46.9 6 14.5 years; eight (72.7%) were male and two (18.2%) were coinfected with HIV. All patients presented with cough whose median duration was 71.1 (interquartile range, 33.1, 109) days. Eight (72.7%) had mild COVID-19 whereas two (18.2%) died, including one with advanced HIV disease. All patients were treated with first-line anti-TB drugs and adjunct therapy for COVID-19 using national treatment guidelines. This report presents the possibility of the coexistence of the two diseases and calls for more vigilance, screening, and collective prevention measures for both COVID-19 and TB.
Keywords: COVID-19; Tuberculosis; Uganda